Simulation study on heat transfer performances of double pipe heat exchanger to recover waste heat in water chiller system - Nguyen , Xuân Viên; Nguyen , Trang Doanh; Doan , Minh Hùng (Journal of Technical Education Science, 2021)
The purpose of this work is to investigate the heat transfer performance of double pipe heat exchanger in a thermal energy storage system (TES). This heat exchanger is installed in the discharge line of compressor in air conditioning water chiller system to recover the waste heat of high temperature refrigerant. The numerical simulation is conducted for double pipe heat exchanger with different mass flow rate of water to investigate for optimal design. The investigation of the heat transfer for double pipe geometry is performed using three dimensional (3D) ANSYS computational fluid dynamics (CFD). This method is based on the fundamental conservation laws of momentum, energy, and mass. The results show the outlet temperature of water increase with decreasing mass flow rate of inlet water. Besides, the outlet temperature of refrigerant also decrease. In addition, the results also indicate the comparison of water outlet temperature between the simulation and experiment.